(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
In this article, it is thought that the metaphor, which is the most viable method of word-building in the Uzbek language, its occurrence through word-building, a number of manifestations of word-building occur in poetic speech and create a variety of artistic visual means.